1997
DOI: 10.1097/00005373-199707000-00027
|View full text |Cite
|
Sign up to set email alerts
|

Specific Features Associated with Femoral Shaft Fractures Caused by Low-Energy Trauma

Abstract: Femoral shaft fractures caused by low-energy violence occur mainly in patients suffering from a chronic disease or a condition causing osteopenia of the femur. The most common fracture pattern was a spiral one in the middle third of the femoral shaft. Despite the low-energy violence, the treatment of these fractures is not devoid of complications. The treatment of these seemingly simple fractures requires careful planning and meticulous operative technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 12 publications
2
26
0
Order By: Relevance
“…However, there is evidence that torsional forces may be involved in many periprosthetic fractures, suggesting torsional loading is pre-eminent in causing periprosthetic femur fracture [30]. A review of femoral shaft fractures caused by low-energy trauma treated over a 10-year period found 58% had a spiral fracture pattern, indicating a torsional mechanism for the fracture [26]. Studies have noted high torsional forces Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is evidence that torsional forces may be involved in many periprosthetic fractures, suggesting torsional loading is pre-eminent in causing periprosthetic femur fracture [30]. A review of femoral shaft fractures caused by low-energy trauma treated over a 10-year period found 58% had a spiral fracture pattern, indicating a torsional mechanism for the fracture [26]. Studies have noted high torsional forces Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In a study from Finland, some specific features of the low-energy femoral shaft fractures which occurred between 1985 and 1994 were described in 50 patients. 87 In this report, bisphosphonate treatment was not considered as a predisposing factor of this type of fracture and very likely no patient of this study was a bisphosphonate user. However, the majority of patients with low-energy femoral shaft fracture had one or more predisposing factors, such as diabetes mellitus, chronic corticosteroid treatment for pulmonary disease or rheumatoid arthritis, and severe osteoarthritis of the ipsilateral hip or knee.…”
Section: Atypical Fractures Of the Femoral Diaphysismentioning
confidence: 91%
“…The latter figure indicates that in the elderly one out of 400 fractures is a low-energy femoral shaft fracture. 87 The authors concluded that a typical lowenergy fracture of the femoral shaft is a closed spiral fracture with minimal comminution in the middle third of the left femur of an aged woman, with a high rate of postoperative complications. It seems that the pattern of the femoral shaft fractures in patients on long-term alendronate therapy described by Goh et al 84 and Kwek et al 86 is different from that of the femoral shaft fractures occurring in non-users of bisphosphonates.…”
Section: Atypical Fractures Of the Femoral Diaphysismentioning
confidence: 99%
“…Fractures located in the subtrochanteric region or femoral shaft (diaphysis) account for 7% to 10% of all hip/femoral diaphyseal fractures. (73,74) Approximately 75% of complete subtrochanteric and femoral shaft fractures are associated with major trauma such as motor vehicle accidents, (73) in which the energy transmitted to the bone results in the propagation of multiple fracture lines, thus producing comminution. Especially in older patients, femoral shaft fractures may occur below the stem of the prosthesis after total hip replacement.…”
Section: Epidemiology Of Subtrochanteric and Femoral Shaft Fracturesmentioning
confidence: 99%
“…(75) In adults of all ages, more than half of femoral shaft fractures are spiral fractures, with the remainder presenting with a transverse or oblique configuration. (73,76) Subtrochanteric fractures have important effects on mortality and morbidity. A study of 87 patients with subtrochanteric fractures showed a mortality rate of 14% at 12 months and 25% at 24 months.…”
Section: Epidemiology Of Subtrochanteric and Femoral Shaft Fracturesmentioning
confidence: 99%